LV-GLS is a predictor of all-cause death and cardiovascular MACE events in patients with neuro-immunological disorders. (14th October 2021) - Khanna, S; Wen, I; Gupta, A; Thakur, A; Bhat, A; Chen, H H L; Gan, G C H; Tan, T C
Abstract: Background: Neuro-immunological disorders encompass several disease states, including multiple sclerosis (MS), autoimmune encephalitis (AE) and myasthenia gravis (MG). These autoimmune conditions are mediated via pro-inflammatory cytokines, and there is growing evidence to suggest cardiovascular involvement within these inflammatory states. Left ventricular global longitudinal strain (LV-GLS) is proposed to be a more sensitive measure of LV systolic function when compared to standard two-dimensional measures such as LV ejection fraction (LVEF). Purpose: The purpose of this study was to assess for subclinical cardiac dysfunction in a cohort of patients with neuro-immunological disorders and correlate this with the development of outcomes on follow-up. Methods: Consecutive patients with MS, AE and MG admitted to our institution during 2013–2020 were assessed (n=102). Patients without pre-existing cardiovascular disease, LVEF <50% or lack of comprehensive transthoracic echocardiography during their index admission were included (n=55). This group was compared to age- and gender-matched controls (n=55) LV-GLS was measured offline using vendor-independent software (TomTec Arena, Germany v4.6) by two cardiologists blinded to the patient group or outcomes. These patients were followed for up for the composite outcome of all-cause death and major adverse cardiovascular events (MACE). Results: A total of 55 patients (31 MS, 14 AE and 10 MG) were age- and gender- matched to 55 controls. There was no significant difference in baseline demographic characteristics or cardiovascular risk factors between groups. Patients with neuro-immunological disorders demonstrated impaired LV-GLS (−17.6±3.5 vs −20.8±1.9; p<0.01) when compared to healthy controls, despite an LVEF within the normal range (60.9±7.7 vs 64.1±5.7; p=0.02) in both groups. There were a total of 9 (16.4%) outcomes during a mean follow-up of 41.0±33.0 months. LV-GLS was the only significant echocardiographic predictor of all-cause death and MACE events (p=0.013) on multi-variate analysis. Conclusions: Our results suggest that patients with neuro-immunological disorders have subclinical LV dysfunction as assessed by LV-GLS which has prognostic capacity in this population. Further larger studies are required to further characterize this phenomenon. Funding Acknowledgement: Type of funding sources: None.